PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP DISIPLIN KERJA DAN PRODUKTIVITAS KERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA INDRAGIRI HILIR - Suhairi Sukma Muflihul; Indarti Sri; Wasnury Rendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This Research aims to understand the influence of work environment and compensation against discipline of work and work productivity employees at indragiri hilir regional water company which is located on m boya street number 7 Tembilahan, Indragiri hilir. Population in this research is allemployees of which consisted of 108 employees and collecting samples using likert scale used to measurea score respondens answer in this research consists of five alternative answers containing another variation. Next use testing instrumental, test the practical and the realibilitas. The method of analysis that used in this research was descriptive analysis and analysis path by exclusively on the spss 23 for windows. This research result indicates work environment and compensation significant impact on discipline work, variable workplace , Compensation and discipline work significant impact on work productivity. The research also showed that the variable work environment and compensation significant impact on work productivity with discipline as intervening variable. The result of the calculation of the coefficient of determination (R2) for first structure is 0.575. It means that the influence of work environment variables and compensation on work discipline is 57.5%. While the rest 42.5% influenced by other variables that had not been included in this model. The result of the calculation of the coefficient of determination (R2) for second structure is 0.734. It means that the effect of work environment, compensation and work discipline on work productivity is 73.4%. While the rest 26.6% influenced by other variables that had not included in this model.Keywords: Work Environment, Compensation, Work Discipline, Work Productivity